Co-crystal Structure of Thermosynechococcus elongatus Sucrose Phosphate Synthase With UDP and Sucrose-6-Phosphate Provides Insight Into Its Mechanism of Action Involving an Oxocarbenium Ion and the Glycosidic Bond - Li, Yuying; Yao, Yuan; Yang, Guosong; Tang, Jun; Ayala, Gabriela Jaramillo; Li, Xumin; Zhang, Wenlu; Han, Qiuyu; Yang, Tong; Wang, Hao; Mayo, Kevin H.; Su, Jiyong (Frontiers in Microbiology, 2020)
In green species, sucrose could help them antagonize abiotic stress. Sucrose phosphate synthase (SPS) is a well-known rate limiting enzyme in the synthesis of sucrose. To date, however, no crystal structure of SPS from green species has been solved. In this study, we report the first co-crystal structure of SPS from Thermosynechococcus elongatus with UDP and sucrose-6-phosphate (S6P). In the catalytic site, the side chains of His158 and Glu331 together with two phosphate groups from UDP make hydrogen bonds with the four hydroxyl groups of the glucose residue in S6P, a scenario that causes these four hydroxyl groups to become partially negatively charged to promote formation of the C1 oxocarbenium ion. Breakage of the hydrogen bond between His158 and one of the hydroxyl groups could trigger a covalent bond formation between the C1 oxocarbenium ion of the S6P glucose moiety and the C2 hydroxyl of fructose-6-phosphate. Consistent with our structural model, we observed that two SPS mutants, H158A and E331A, lost all catalytic activity. In addition, the structures of two loops (loop1 and loop2) in the SPS A-domain could not be solved. B-factor analysis and the molecular dynamics stimulations of the full-length enzyme and A-domain indicated that both loops are crucial for binding and releasing substrate and product. In addition, temperature gradient analysis shows that this SPS exhibits its highest activity at 70 ℃, suggesting that this enzyme has the potential of being used in industrial production of sucrose.